Factors Influencing Low Interest of Fertile Women in Undergoing IVA Tests at Butong Community Health Center (STIKES Columbia Asia Medan, 2025)
A condition of physical and mental well-being devoid of all illnesses pertaining to the reproductive system, reproductive function, and reproductive processes is known as reproductive health. Women's reproductive health is therefore crucial. Cervical cancer brought on by an infection with the Human Papillomavirus (HPV) is one illness that can compromise the health of reproductive organs. 95% of occurrences of cervical cancer are linked to HPV, which is spread through sexual activity. Cervical cancer is presently the second most common cause of death for women's reproductive health, after breast cancer. After cardiovascular illness, cancer is the second most common cause mortality. There are number of ways to prevent cervical cancer, including IVA (Visual Inspection with Acetic Acid), a test that uses 3-5% acetic acid in a speculum and is visible with the unaided eye. However, many women still refuse to undergo the IVA test. In order to promote early detection behavior, husbands' knowledge, attitudes, and support are crucial. Counseling is one way to raise public awareness and interest. The purpose of this study is to identify the variables that affect fertile women's lack of interest in having IVA exams. The chi-square test version 25.0 was employed in the analysis. According to the test findings, there is a correlation between husband's support (p-value = 0.010), attitudes (p-value = 0.010), and knowledge (p-value = 0.006). The study concludes that women of reproductive age's lack of interest in undergoing IVA tests at the Butong Health Center is influenced by knowledge, attitudes, and husband support.